Prevajanje ljudskih pesmi in umetne poezije z medbesedilnim navezovanjem na ljudsko izročilo - Mugerli Lavrenčič, Maruša (Jezik in slovstvo, 2006)
Translation of folk songs differs considerably from translation of literary poetry; this is mainly due to the differences between folk songs and literary poetry. Translators of Slovene folk songs have opted for various translation strategies when trying to present Slovene heritage to foreign readers. That translation is not simply a transfer from one language to another, but also, and above all, from one culture to another, is not testified only by the translation of folk songs, but also by literary poetry, which is related intertextually, therefore continuing the Slovene tradition, whose meaning, however, is quite often lost in translation.
Keywords: intertekstualnost; Intertextuality; literarne študije; prevajanje; slovenske ljudske pesmi; translation